„Wy oświeceni, my dzicy ludzie jesteśmy, ale my więcej od was umiemy”. Postacie operowe Wojciecha Bogusławskiego w obliczu utraty wolności - Maksymowicz, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
This article constitutes an attempt at recreating the possible allusive readings, political references and hidden meanings in three operas by Wojciech Bogusławski: Dla miłości zmyślone szaleństwo (Madness made for love), Axur król Ormus (Axur, the king of Ormus), Izkahar król Guaxary (Izkahar, the king of Guaxara). Key for this search are the attitudes of the characters in the analysed operas towards the loss of freedom – one may argue that their ways to cope with the violence and the ruthless autocratic tyranny could be perceived as contemporary. This is why the story, which is in its outer layers one of an unhappy love, became for the eighteenth-century viewers a story of the most important contemporary politics.